Medicinal Plants - Kumar, Sanjeet (IntechOpen, 2022)
This book, Medicinal Plants, provides a comprehensive overview of plant species helpful for treating and preventing human diseases and disorders. It also discusses how to obtain sustainable healthcare systems from nature and make harmony with currently available medicinal wealth, ecology, and the community.